Roma y la epigrafía ibérica sobre piedra del nordeste peninsular (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Review of the polemic about the role of Roman influence in the development of Iberian epigraphy on stone in north-eastern Hispania during the 2nd and 1st cent. BCE. Two models are suggested: one in the Mediterranean harbours of Emporion, Tarraco and Saguntum, three cities with a strong Roman presence or influence, where the principal concentrations of Iberian epigraphs are located along with other Latin —and Greek— inscriptions, and Roman epigraphic types arise in a monumental context; and another one in the rest of the Iberian north-eastern regions where stelae predominate as local response to the Roman inspired monumentalisation of the coastal cities. The emergence of Iberian inscriptions on stone is explained asa consequence of the process of romanization and the diffusion, in this context, of the incipient Roman epigraphic culture.
Keywords: Iberian Inscriptions on Stone; Iberian Stelae; Latin Epigraphy in Hispania; 2nd-1st Cent. BCE